Experiences of countertransference in beginning psychotherapists. - Peers, Robert (My University, 2013)
Given the rise of intersubjective theory (Marzi, Hautman & Maestro, 2006) and contemporary formulations of countertransference as an integral aspect of the psychotherapeutic process (Cassorla, 2005; Marchon, 2006), understandings of countertransference are still being developed and explored in the psychoanalytic literature. This study explores beginning psychotherapists’ experiences and understandings of countertransference and countertransference-related phenomena. In depth data was obtained from five volunteer psychotherapists in their first three years of practice who were interviewed using a semi-structured interview schedule. These interviews were analysed using a psychoanalytically informed narrative methodology. The need for an experiential model of countertransference that remains true to the often alive, elusive and indescribable nature of countertransference experiences was a central finding of the project. A secondary focus of the research was the therapists’ development of their sense of professional identity. The paucity of research exploring the interaction of countertransference and professional identity development rendered this an important area of investigation. The effect of this process upon the way in which the beginning psychotherapists made sense of their countertransference experiences, was a finding of further significance.
Keywords: Countertransference (Psychology).; Psychotherapists--South Africa.